2021
DOI: 10.1093/mnras/stab097
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric circulation of brown dwarfs and directly imaged exoplanets driven by cloud radiative feedback: global and equatorial dynamics

Abstract: Brown dwarfs, planetary-mass objects and directly imaged giant planets exhibit significant observational evidence for active atmospheric circulation, raising critical questions about mechanisms driving the circulation, its fundamental nature and time variability. Our previous work has demonstrated the crucial role of cloud radiative feedback on driving a vigorous atmospheric circulation using local models that assume a Cartesian geometry and constant Coriolis parameters. In this study, we extend the models to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 114 publications
4
46
0
Order By: Relevance
“…Tan and Showman (2017) included a parameterization of silicate condensation and latent heating in their GCM study and found that isolated silicate storms can occur when the condensation level sinks below the radiative‐convective boundary due to the onset of moist convection, which could explain the inferred patchiness of clouds and temporal variability of objects at the L‐T transition. Variability is also likely impacted by the rotation rate and cloud radiative feedback (Tan & Showman, 2019, 2020, 2021), such that changes in the Coriolis force with latitude could lead to corresponding changes in cloud opacity and patchiness inline with observations of brown dwarfs at different inclinations, where objects viewed equator‐on are redder and more variable than objects viewed pole‐on (Vos et al., 2017).…”
Section: Insights From Theorymentioning
confidence: 91%
“…Tan and Showman (2017) included a parameterization of silicate condensation and latent heating in their GCM study and found that isolated silicate storms can occur when the condensation level sinks below the radiative‐convective boundary due to the onset of moist convection, which could explain the inferred patchiness of clouds and temporal variability of objects at the L‐T transition. Variability is also likely impacted by the rotation rate and cloud radiative feedback (Tan & Showman, 2019, 2020, 2021), such that changes in the Coriolis force with latitude could lead to corresponding changes in cloud opacity and patchiness inline with observations of brown dwarfs at different inclinations, where objects viewed equator‐on are redder and more variable than objects viewed pole‐on (Vos et al., 2017).…”
Section: Insights From Theorymentioning
confidence: 91%
“…This may be an acceptable prior if truly nothing is known about the typical angular scale of features on the surface, but this is seldom the case. Both observations of the Sun and magnetohydrodynamic simulations of stellar magnetic fields give us prior constraints on the typical scales of starspots (e.g., Berdyugina 2005;Solanki et al 2006), and climate models of brown dwarfs tell us about typical sizes of clouds and other atmospheric features (e.g., Tan & Showman 2019, 2021a. These can be encoded into our Gaussian prior by choosing a prior variance that scales with spherical harmonic degree, as in Equation ( 31), where the variance at each degree is parametrized as, e.g.,…”
Section: Gaussian Priorsmentioning
confidence: 99%
“…Radiative transfer equations including multiple scattering are solved with a two-stream approximation (Kylling et al 1995). A similar numerical implementation has been applied to GCMs of exoplanets and brown dwarfs (Komacek et al 2017;Tan & Showman 2021). An internal heat flux of 7.48 W m −2 (Li et al 2018b) is also added as a radiative flux at the bottom of our model.…”
Section: Jupiter 2d Radiative-dynamical Modelmentioning
confidence: 99%